Pengaruh Pembelajaran Matematika Dengan VBA Excel Terhadap Motivasi dan Hasil Belajar Siswa: VBA Excel, Motivasi Belajar, Hasil Belajar - Eliza Maria Fitri; Masjudin Masjudin; Baiq Rika Ayu Febrilia (Jurnal Kependidikan Ki Hajar Dewantara, 2024)
The purpose of this study was to determine the effect of learning mathematics with VBA Excel on student motivation and learning outcomes. The type of research used is experimental research with a quantitative approach. The sample selected in this study were 42 students from class VII MTs Tarbiyatul Qurro' Selagalas, Mataram City. The instruments used in this study were in the form of description questions and questionnaire instruments. The data analysis technique used is the T test. Before carrying out the T analysis, a prerequisite test must be carried out, namely reliability, homogeneity and normality tests.The results of the analysis of student learning outcomes data that have been carried out show values ​​> -4.601 and -1.729 because > = -4.610 > -1.729. For the analysis of student learning motivation, the results obtained were > -22.194 and -1.684. Because > = -22.194 > -1.684, H0 was rejected while H1 was accepted with a significant level of 5%, it means that there is mathematics learning on student motivation and learning outcomes.